There Is No Relation between Epitympanic Recess Volume and Chronic Otitis Media - Fatma Dilek Gokharman; Omer Kocak; Baris Irgul; Pinar Kosar; Sonay Aydin (Tomography, 2023)
Background: Chronic otitis media is recurrent infection of the middle ear and mastoid air cells in the setting of perforation of the tympanic membrane. Risk factors for chronic otitis media include predisposing characteristics such as gender, allergies, Eustachian tube dysfunction, history of acute otitis media, and upper respiratory tract infection. The purpose of this study was to evaluate the potential relationship between chronic otitis media and epitympanic recess volume. Materials and Methods: A total of 197 patients with chronic otitis media had their epitympanic recess volume compared to the epitympanic volume of 99 healthy controls. The epitympanic recess volume was measured via the 3D volumetric measurement tool of the local PACS. Epitympanic recess volume measurement was performed using axial sections in a plane starting from the level of the malleus head–anvil body in the craniocaudal direction to the tegmen tympanum. Results: It was shown that patients with bilateral involvement had an epitympanic recess volume of 75.00 mm3, compared to 72.30 mm3 in those with unilateral chronic otitis media. The healthy control group’s median value for the epitympanic recess was 74.73 mm3. Conclusions: Epitympanic volume values did not differ substantially between patients with chronic otitis media and healthy persons, and epitympanic volume was not recognized as a predisposing factor (p = 0.686).